Selection of fungi for accelerated decay in stumps of Eucalyptus spp. - de Andrade, Frederico Aguirre; Calonego, Fred Willians [UNESP]; Durgante Severo, Elias Taylor [UNESP]; Furtado, Edson Luiz [UNESP] (Elsevier B.V., 2012)
The objective of this study was to select decay fungi for biological degradation of stumps and roots from Eucalyptus spp. in forest stands. Five fungal isolates were cultured. Subsequently, inoculated in accelerated-decay tests and field tests with tree stumps of Eucalyptus spp. present in a stand belonging to Votorantim Company were conducted. The results showed that: (1) the decay of stumps by Pycnoporus sanguineus and Ganoderma applanatum increased by up to 49.2% and 48.9%, respectively; (2) the enclosing stumps in a polyninyl chloride resulted in a reduced on the resistance due to enhanced decay as measured by an inpact penetrometer in the forest stands at Luiz Antonio, Capao Bonito, and Jacarei, SP, Brazil; and (3) the selected fungi did not show any pathogenic potential toward seedlings and adult trees. This study presents the foundation for the development of a biological system for stump removal in forest stands comprising Eucalyptus spp. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Biological degradation of stumps; Eucalyptus grandis; Wood-decaying fungi; Ganoderma applanatum; Pycnoporus sanguineus